1990
DOI: 10.1063/1.104087
|View full text |Cite
|
Sign up to set email alerts
|

Powder-free plasma chemical vapor deposition of hydrogenated amorphous silicon with high rf power density using modulated rf discharge

Abstract: Deposition of hydrogenated amorphous silicon films from SiH4/He gas mixtures was performed by using a square wave amplitude modulated rf discharge. The modulation was used for controlling radical densities in plasmas which led to a high rate deposition of good quality films. The fairly high deposition rate of 6 Å/s was obtained for a low concentration of 5% SiH4 and a high rf peak power 200 W (0.8 W/cm3) without any appreciable amount of powder particles in the reaction chamber. The optical gap of the films wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Particle formation in rf silane plasmas is strongly reduced by square-wave power modulation at kHz frequencies [ 10,15,25]. In previous work [7,9,15] with plasma conditions suitable for high quality amorphous silicon deposition, we demonstrated that powder does not form when anions are observed to escape (modulation frequency < 3 kHz), and that powder does form when the anions do not have time to be evacuated in the afterglow (modulation frequency > 3 kHz).…”
Section: Exderimental Evidence For Negative Ions As Powder Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particle formation in rf silane plasmas is strongly reduced by square-wave power modulation at kHz frequencies [ 10,15,25]. In previous work [7,9,15] with plasma conditions suitable for high quality amorphous silicon deposition, we demonstrated that powder does not form when anions are observed to escape (modulation frequency < 3 kHz), and that powder does form when the anions do not have time to be evacuated in the afterglow (modulation frequency > 3 kHz).…”
Section: Exderimental Evidence For Negative Ions As Powder Precursorsmentioning
confidence: 99%
“…Other pathways may predominate in high power (-0.8 W cm-3), high pressure (-1 mbar) silane plasmas in which particle formation occurs in a fraction of a second [25,26]. Mandich and Reents [18] disqualify positive ions since bottlenecks occur in cation nucleation (although exceptions exist [ 19,271) and furthermore they are rapidly lost by evacuation across the plasma sheaths.…”
Section: Neutral and Cation Cluster Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Watanabe et al 1990, Bouchoule et al 1991, Fukuzawa et al 1994, Howling et al 1994, and Schmidt et al 1993). In addition, the amount and location of particulates is highly dependent on the details of each individual deposition chamber.…”
Section: Light Scattering Observationsmentioning
confidence: 99%
“…It may be possible to prevent these from growing to the 2-20 nm size range, for example by modulating the discharge and allowing the R nm particles to leave periodically (e.g. Watanabe et al 1990). However, many of these small particles will deposit into the film, probably with undesirable consequences.…”
Section: Model For Particle Deposition During Film Growthmentioning
confidence: 99%